2019
DOI: 10.1111/ocr.12289
|View full text |Cite
|
Sign up to set email alerts
|

Alignment efficiency of coaxial tubular superelastic nickel‐titanium vs single‐stranded superelastic nickel‐titanium in relieving mandibular anterior crowding in extraction cases: A single‐centre randomized controlled clinical trial

Abstract: Structured Abstract Objectives To compare the alignment efficiency of coaxial tubular and single‐stranded 0.016” superelastic NiTi archwires in relieving mandibular anterior crowding in extraction cases and to evaluate whether alignment efficiency differed as the initial irregularity increased. Setting and Sample Population Forty female patients aged between twelve and twenty years from the postgraduate orthodontic clinic at the authors’ centre. Materials and Methods All patients in this single‐centre, 2‐arm p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
(38 reference statements)
0
2
1
1
Order By: Relevance
“…In contrast to the present study, Sebastian et al [ 17 ] reported 6.17 mm and 4.88 mm reduction in the irregularity index in the anterior site of the lower dental arch by using coaxial tubular SENT and single-stranded NiTi archwires, respectively, which were considerably greater than the values reported in the present study. It appears that lower mean age in their study may be an important factor explaining the difference between their results and ours, because it has been demonstrated that age significantly affects the success of orthodontic tooth movement [ 22 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the present study, Sebastian et al [ 17 ] reported 6.17 mm and 4.88 mm reduction in the irregularity index in the anterior site of the lower dental arch by using coaxial tubular SENT and single-stranded NiTi archwires, respectively, which were considerably greater than the values reported in the present study. It appears that lower mean age in their study may be an important factor explaining the difference between their results and ours, because it has been demonstrated that age significantly affects the success of orthodontic tooth movement [ 22 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, Nabbat and Yassir [ 16 ] reported equal efficacy of heat-activated NiTi (HANT) archwire and SENT archwire for alignment of the teeth. Sebastian et al [ 17 ] reported that coaxial tubular and single-stranded SENT archwires were equally effective for correction of crowding of the anterior site of the lower dental arch. Moreover, Nordstrom et al [ 18 ] demonstrated equal efficacy of TiNbTaZr and the conventional NiTi archwires for alignment of the teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Brough et al Demostraron en su artículo de 2010 que la morfología, el tamaño y la forma de los caninos pueden tener un efecto intenso en el atractivo de la sonrisa percibida entre la población general, los dentistas los ortodoncistas. (Sebastian et al, 2019).…”
Section: Discussionunclassified
“…It surpasses singlestranded superelastic NiTi in several ways such as shorter treatment duration, greater springback, resistance to permanent deformation, and a low-force delivery [20]. The flexibility of the wire is increased by a "hollow center" design that allows the archwire to fold on itself so full engagement in the severe malalignment can be performed while applying less amount of force than the conventional initial archwires [21].…”
Section: Figure 1 -Force Levels Of Nickel-titanium Initial Archwires ...mentioning
confidence: 99%